Genetic variability for yield and related traits among wild accessions of cowpea and cross-compatibility with cultivated accessions - Olayiwola Richard Oluseyi; Taiwo Bolaji Samuel; Oyetunde Oyeboade Adebiyi; Ariyo Omolayo Johnson (Agricultura Tropica et Subtropica)
Cowpea is an important legume, and its wild relatives could be reliable sources of favorable alleles for genetic diversity and improvement of important traits. The study aimed to evaluate wild accessions of cowpea for genetic variability, identify important traits focused on yield and yield components, and assess wild and domesticated cowpea genotypes for cross-compatibility. Forty-four accessions of wild relatives and domesticated cowpeas were used for the study. Forty wild accessions were evaluated for genetic variability, and selected accessions were crossed with domesticated cowpea accessions. The experiment was laid out in a randomised complete block design with three replicates. The data collected were subjected to analysis of variance (ANOVA), and correlation coefficients between characters were calculated. Furthermore, data were subjected to factor analysis, step-wise regression, and selection criteria were calculated. The genotypic effect was significant (p < 0.01; p < 0.05) for most of the measured characters except the number of branches per plant. Factor analysis showed that seed yield and number of pods per plant mainly contributed to the observed variations among the wild relatives. The number of pods per plant was among the characters that had positive and significant phenotypic and genotypic correlations with seed yield. Step-wise regression identified the number of pods per plant as the main contributor to variations in seed yield. NGB001071 was identified as one of the top accessions by the classical selection index, largely due to its relatively higher number of pods per plant and seed yield. Crosses between wild accessions and domesticated cowpea were successful. The potential of introgression of favourable alleles from wild forms to domesticated cowpea was documented. This finding suggests that leveraging wild germplasm could enhance the resilience and genetic diversity of cowpeas for measured characters, ultimately improving yield and adaptability to changing environmental conditions.